Le récit biographique face à la grande Histoire : « Les éblouissements » de Pierre Mertens - Lis, Jerzy (Studia Romanica Posnaniensia, 2012)
Pierre Mertens’ novel Les éblouissements, published in 1987, is a fictionalised biography of a famous German poet Gottfried Benn, who made the biggest mistake of his life agreeing to support the National Socialist regime during several months. Mertens reconstructs the poet’s life trying to understand the reasons of his commitment, considered by the intellectuals of that time to be a betrayal. Mertens’ text is an illustration of the relationship between the individual and the historical past and, at the same time, an example of problemising the biographical factor in relation to Great History. Playing with the double signification of the word ‘éblouissement’, the novelist offers his own interpretation of the German poet’s double life.